2013
DOI: 10.1380/ejssnt.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pt(IV) and Pd(II) from Aqueous Solution by Calcined Gibbsite (Aluminum Hydroxide)

Abstract: In the present study, calcined gibbsite (GB) was prepared by calcination treatment between 200 and 1000 • C (GB200-GB1000). The properties of GBs (i.e., the amount of hydroxyl groups, specific surface area, mean pore diameter, and pore volume) were evaluated. GB400 had the highest amount of hydroxyl groups (0.46 mmol/g), as well as the highest specific surface area (295.3 m 2 /g) and micropore volume (0.036 mL/g). It also provided the highest amount of the adsorbed Pt(IV) and Pd(II), which suggests that the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…The higher selectivity for Pd 2+ ions in comparison to other noble metal ions may be due to the geometry square planar of Pd 2+ , which allows its fast adsorption, while more complex structures such as Pt 4+ and Au 3+ might require a longer time to be adsorbed. Similar phenomenon can be seen in the adsorption of platinum metal ions on other group metals (Pd, Pt, Rh) Fe 3 O 4 [40]. In general, the competitive adsorption ability varies from one metal ion to another and is related to a number of factors such as molecular mass, ion charges, hydrated ionic radius, and the hydration energy of the metals [41].…”
Section: Simultaneous Removal Of Various Metal Ionssupporting
confidence: 53%
“…The higher selectivity for Pd 2+ ions in comparison to other noble metal ions may be due to the geometry square planar of Pd 2+ , which allows its fast adsorption, while more complex structures such as Pt 4+ and Au 3+ might require a longer time to be adsorbed. Similar phenomenon can be seen in the adsorption of platinum metal ions on other group metals (Pd, Pt, Rh) Fe 3 O 4 [40]. In general, the competitive adsorption ability varies from one metal ion to another and is related to a number of factors such as molecular mass, ion charges, hydrated ionic radius, and the hydration energy of the metals [41].…”
Section: Simultaneous Removal Of Various Metal Ionssupporting
confidence: 53%
“…Moreover, the pseudo-second-order rate constant (k 2 ) of Pt(IV), Pd(II), and Mo(VI) adsorption on GB400 was greater than that of Au(III) adsorption, which suggest that GB400 was suitable for adsorption of Au(III) compared to Pt(IV), Pd(II), and Mo(VI). 27,17 Therefore, the data obtained in this study were characterized significantly better by the pseudo-secondorder model with respect to the pseudo-first-order model. The adsorption equilibrium of Au(III) between aqueous solution and GB400 can be described by an adsorption isotherm.…”
Section: Resultsmentioning
confidence: 69%
“…This study also observed a similar trend: the specific surface area and micropore volume showed a positive correlation. 17 Figure 1 shows the pH drift test for GB400. The pH of the zero charge, pH pzc , corresponds to that at which the curve crosses the straight line that fits the points pH initial = pH final .…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous studies. [20][21][22] Figure 2 shows XRD patterns of Al, Ni, and NA11. These demonstrate that Al, Ni, and NA11 have structures similar to gibbsite, β-Ni(OH) 2 , and nickel hydroxide, respectively.…”
Section: Resultsmentioning
confidence: 99%